2015
DOI: 10.1002/ps.4149
|View full text |Cite
|
Sign up to set email alerts
|

Volatilisation of pesticides under field conditions: inverse modelling and pesticide fate models

Abstract: Volatilisation of propyzamide, pyrimethanil, chlorothalonil, diflufenican, tolylfluanid, cyprodinil and E- and Z-dimethomorph from crops under realistic environmental conditions can be modelled with the PEARL model, as corroborated against field observations. Suggested improvements to the volatilisation component in PEARL should include formulation attributes and leaf wetness at the time of pesticide application. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 63 publications
0
7
1
Order By: Relevance
“…Notably, there was almost no weight loss with PILs 3 and 5, which had lower melting points, during the 12 h of the test. However, the volatilization percentage of PIL1 (12.24%) was higher than that of PYR (11.78%), which was not in accordance with a preceding study that reported that fatty acids showed considerable potential to reduce volatilization of pesticide ions . This result could be attributed to the higher volatilization of its counter anion.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…Notably, there was almost no weight loss with PILs 3 and 5, which had lower melting points, during the 12 h of the test. However, the volatilization percentage of PIL1 (12.24%) was higher than that of PYR (11.78%), which was not in accordance with a preceding study that reported that fatty acids showed considerable potential to reduce volatilization of pesticide ions . This result could be attributed to the higher volatilization of its counter anion.…”
Section: Resultscontrasting
confidence: 89%
“…However, the volatilization percentage of PIL1 (12.24%) was higher than that of PYR (11.78%), which was not in accordance with a preceding study that reported that fatty acids showed considerable potential to reduce volatilization of pesticide ions. 36 This result could be attributed to the higher volatilization of its counter anion. The trend on the results of the PILs paired with different anions indicated that the volatility was related to the structure of the anion.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer rates of OCDPE from prepared tea to the infusion were 6.0–14.8 %; the mean value of which was 8.98 %. The transfer efficiency of the pesticide residue into the infusion depends on its water solubility, partition coefficient, and low vapor pressure (Iizuka and Shimizu 2014; Fantke et al 2012; Houbraken et al 2016). Based on the present research, the lower transfer rate of OCDPE from prepared tea to the infusion may be due to its hydrophobic character (insolubility in water) and high vapor pressure.…”
Section: Resultsmentioning
confidence: 99%
“…air velocity and turbulence) and surface properties (e.g. temperature and roughness) (Leistra and Wolters 2004; FOCUS 2008; Lichiheb et al 2014; Houbraken et al 2016). We used default values of 0.06 and 0.1 cm for the thickness of the boundary air layers on plant leaves and soil surfaces, respectively (van den Berg et al 2016); sensitivity of rate of pesticide volatilisation to the value of d (Fig.…”
Section: Methodsmentioning
confidence: 99%